Car plate recognition system : (segmentation) - Nor Helmy Effendy, Meon (2005)
Nowadays, there are many researches on pattern recognition. Therefore,the purpose of this research is to develop a prototype by referring the University College of Engineering & Technology of Malaysia (UTEC) as the case study.The use of human workforce for the safety control in UTEC really cannot be implemented consistently and effectively since human ability is limited.Therefore, the development of the safety prototype is a stepping-stone to ensure that the safety control is getting better.The prototype is a car plate recognition prototype based on the acquired car plate image. However, in this research, it only focuses on two phases of the recognition phase which are car plate thinning phase and car plate segmentation phase.The technique that was used in every phase is based on the algorithms that are developed by previous researchers. In the research,One Pass Thinning algorithm and Partial Segmentation algorithm are the algorithms being applied.For each phase,the used technique produces quite a good result whereby it is to be discussed in detail in the thesis.